Aktivitas Komunikasi Kelompok dalam Tradisi Lelang Pesta Pernikahan Adat Desa Kalampadu Kecamatan Muara Kuang Kabupaten Ogan Ilir - Rukmana Sari; Choiriyah Choiriyah; Manalullaili Manalullaili (Jurnal Komunikasi Islam dan Kehumasan (JKPI), 2018)
Group communication as face-to-face interaction of three or more individuals in order to obtain the desired intent or purpose such as a variety of information, self-maintenance or problem solving so that all members can grow the personal characteristics of other members accurately. Tradition is something that has been done for a long time and becomes part of the life of a community group, usually from a country, culture, time, or religion. This thesis is entitled "Activities of Group Communication in the Lelang Tradition Wedding Party of Kalampadu Village, Muara Kuang, Ogan Ilir”. The formulation of the problem in this thesis are how to activities of group communication in the lelang tradition wedding party and how are the inhibiting factors of group communication in the lelang tradition wedding party of Kalampadu village. The type of data in this study is qualitative data, the data sources are primary and secondary data. Data collection is done by observation, interviews and documentation. After the data is collected, the data is analyzed by qualitative descriptive data analysis techniques. The results of the research are: There are communication between families of the two brides, communication between the family of the bride and groom to the community, communication between brides and brides with the band. The inhibiting factors in group communication in the auction tradition include: Economy and Solidarity.